The Relationship between Work Environment Factors and Training Transfer - Yap,, Chiew Lan. (Universiti Malaysia Sarawak, UNIMAS, 2010)
The research aims to identify the relationship between work environment factors and training transfer. Th e research was quantitatively design to identify the relationship between work environment factors ( accountability, workload, strategic linkage and opportunity to perform) and training transfer. Research was conducted at one of the local organization that always provide training program to its employees. Th ere were 65 respondents who involved in th e research. From the reliability and validity analysis, it was indicated that the finding s of research was valid and rel i a ble. Findings of research reviewed that high training transfer was existed among the respond ent of this researc h . Based on the r esults of hypotheses testing , it was indicated that there were positive relationship between wrok environment factors and training transfer. This result showed the important of work environments factors on training trans fer and concerned must be put on to these factors during the implementation of training program. Lastly, the research was end with the limitation of study and recommendation for organization and future research.